Analysis of Measurements Results of the Ground Vibration Induced By Blasting During the Tunneling for Istanbul Subway in Turkey - Ali Kahriman; Savas Gorgun; Abdulkadir Karadogan; Simav Bargu; Gungor Tuncer; Esat Tansev; Derya Kucukbrtem (International Society of Explosives Engineers, 2002)
Although many research studies had been carried out in the past in order to eliminate environmental issues produced from blasting unfortunately a general approach or formula has not been established yet because of the complexity of the matter. In addition to the wave and ground motion characteristics, the complexity of blasting parameters and site factors restrict the developing of a general criterion. So experimental site-specific studies should be still done in order to predict and control blasting effects.